A monolithic sandwich panel for insect-mimicking micro drones. (February 2020) - Jeong, Yoon Chang; Kang, Kiju
Abstract: Recently, insect-mimicking micro-drones have attracted attention owing to their numerous potential applications. For use as the exoskeletons of these micro-drones, a monolithic sandwich panel with a total thickness of 1 mm was fabricated in this study via a novel technique employing metallic foil with a microlattice core. The face sheets were appropriately designed to be thicker than the foils comprising the core to obtain high failure moments and flexural rigidities. Using this approach, we successfully realized mechanical properties superior to those of the elytra of beetles at a comparable areal density. The mechanical behaviors of the panels were evaluated via theory and finite element analysis (FEA), and the optimal combinations of the two thicknesses of the foils comprising the face sheets and the cores for achieving the maximum strengths for the given areal densities were identified. The sandwich panels are expected to have sufficiently high failure moments and rigidities even with half-height cores, exhibiting great potential for use in insect-mimicking micro-drones. Graphical abstract: Unlabelled Image Highlights: For use in micro-drones, a sandwich panel as thin and light as beetle elytra is necessary. We fabricated a metallic microlattice-cored sandwich panel with thicker face sheets. Bending properties superior to those of the elytra of beetles were successfully realized. Optimal design was determined to achieve the highest strength for a given areal density.